Overview Tumour Disease and Oncologic Therapy During Pregnancy - Findeklee, Sebastian (Zeitschrift für Geburtshilfe und Neonatologie, 2018)
Newly diagnosed cancer in pregnancy is an issue with increasing importance, because fulfilling the wish to have a child is shifted later in life. Tumour disease is diagnosed in around 0.1% of all pregnancies in Germany. Most common tumour entities involve the breast, the cervix and the hematopoietic system. As tumour prognosis is not negatively affected by pregnancy and gestation does not disclude oncologic therapy it is important to plan treatment immediately. Oncologic surgery preserving the uterus is not at all limited. Chemotherapy with anthracyclines, taxanes or platinum derivates is possible from the second trimenon on. Only radiotherapy should be avoided during pregnancy. Before initiating therapy, fertility preserving methods like cryopreservation of oocytes and/or ovarian tissue should be offered to the patient. Preterm birth is more common in women with a first diagnosis of cancer during pregnancy. Other negative effects on the child’s future are not yet known. Treatment of pregnant cancer patients should be handled by experienced centres with a multi-professional team.
Keywords: pregnancy; tumour disease; oncofertility